Discovery of a new Namurian archaeorthopterid from Ningxia, China (Insecta: Archaeorthoptera) - Liu, Yushuang; Ren, Dong; Prokop, Jakub (Zootaxa, 2009)
A new archaeorthopterid Chenxiella liuae gen, et sp. nov. is described from the Upper Carboniferous (Namurian B-C) of the Tupo Formation in Ningxia Hui Autonomous Region (China). The new taxon exhibits a unique combination of wing venation characters. Together with other described archaeorthopterids, this new specimen further demonstrated considerable diversity of this group in Namurian ecosystems. However, C. liuae gen. et sp. nov. (uncertain family assignment) makes the higher systematics and classification of Archaeorthoptera more complicated and difficult.